(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2011)
Customary Law has been at the forefront of Constitutional Court applications and verdicts for the last decade. Custom and traditions are increasingly criticized for not conforming to the social morals of our society and an increasing number of communities are faced with law suites regarding the unconstitutionality of the practicing of entrenched customs and traditions. The 1921 Van Breda-test for a custom to be recognized as having legal and social applicability has been called into question by various South African Courts. These requirements have been identified as being too rigid, incapable of change negating the customs and society it wishes to conform or represent. In Shilubana and others v Nwamitwa (2009) the court held that legislation had to be formulated to substitute the current inadequate requirements for the validity of a custom. These requirements must reflect the changing face of custom and grant this norm- structure its rightful place in jurisprudence.